ASPECTS OF SCOLIOSIS RECOVERY BY ORTHOSING IN PREPUBERTY - Mihai Constantinescu (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2018)
This article refers to some general aspects regarding the approach of scoliosis recovery programmes aimed at prepubertal children aged between 10-14, by the uses of brace-type orthoses.